Anti-inflammatory, Antinociceptive, and Antioxidant Activities of Methanol and Aqueous Extracts of Anacyclus pyrethrum Roots - Manouze, Houria; Bouchatta, Otmane; Gadhi, A. Chemseddoha; Bennis, Mohammed; Sokar, Zahra; Ba-M’hamed, Saadia (Frontiers in Pharmacology, 2017)
Anacyclus pyrethrum (L.) is a plant widely used in Moroccan traditional medicine to treat inflammatory and painful diseases. The objective of the present study was to evaluate the antinociceptive, anti-inflammatory and antioxidant activities of aqueous and methanol extracts of Anacyclus pyrethrum roots (AEAPR and MEAPR). The anti-inflammatory effect of AEAPR and MEAPR was determined in xylene–induced ear edema and Complete Freund’s Adjuvant (CFA)-induced paw edema. The antinociceptive activity of AEAPR and MEAPR (125, 250 and 500 mg/kg) administered by gavage was examined in mice by using acetic acid-induced writhing, hot plate, and formalin tests, and the mechanical allodynia were assessed in CFA-induced paw edema. In addition, the in vitro antioxidant activities of the extracts were determined by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method, ferric reducing power and β-carotene-linoleic acid assay systems. AEAPR and MEAPR produced significant reductions in CFA-induced paw edema and xylene-induced ear edema. A single oral administration of these extracts at 250 and 500 mg/kg significantly reduced mechanical hypersensitivity induced by CFA, which had begun 1h30 after the treatment, and was maintained till 7 hours. Chronic treatment with both extracts significantly reduced mechanical hypersensitivity in persistent pain conditions induced by CFA. Acute pretreatment with AEAPR or MEAPR at high dose caused a significant decrease in the number of abdominal writhes induced by acetic acid injection (52.2% and 56.7%, respectively), a marked increase of the paw withdrawal latency in the hot plate test, and also a significant inhibition of both phases of the formalin test. This antinociceptive effect was partially reversed by naloxone pretreatment in the hot plate and formalin tests. Additionally, a significant scavenging activity in DPPH, reducing power and protection capacity of β-carotene was observed in testing antioxidant assays. The present study suggests that AEAPR and MEAPR possess potent anti-inflammatory, antinociceptive and antioxidant effects which could be related to the presence of alkaloids and phenols in the plant. In addition, the antinociceptive effect of APR extracts seems to partly involve the opioid system. Taken together, these results suggest that Anacylcus pyrethrum may indeed be useful in the treatment of pain and inflammatory disorders in humans.